Affordances de ambientes informais para a aprendizagem de língua inglesa - Giovana Garcia Gonçalves Gutierrez (2020)
Learning English can happen in different ways in both formal and informal environments. In the contemporary context, digital technologies influence the way we learn due to their accessibility and ubiquitous nature (COPE; KALANTZIS, 2010). In the light of such changes, the informal learning of English has been a growing and still little investigated practice in the technological scenario. Besides that it is necessary to understand the effects of informal learning on learners' perceptions such as its contributions and limitations. To achieve this goal, I investigated the affordances (GIBSON, 1986) of informal English learning in narratives produced in an undergraduate subject of the Languages course at UFMG. As a result of the data analysis, the following affordances have emerged from the participants' interaction with the informal environments: watching films and TV series, using smartphones, exploring music, playing games, talking to foreigners, watching YouTube videos and reading books. In addition, learners also indicated the limitations of such environments, which are: absence of a teacher, lack of grammatical content, lack of formal language, youth focused environments and lack of authentic context. In response to these findings, it was possible to conclude that informal English learning is intertwined with beliefs that are grounded in formal learning. There were two recurrent beliefs, the first related to informal learning as an entertaining practice in opposition to the formal classes considered by the participants to be boring. The second belief was related to the need of both informal and formal environments in order to learn English highlighting the role of traditional teaching despite its limitations. Therefore, informal learning was seen as important to improve English’ aspects such as listening comprehension, pronunciation, vocabulary, idioms, cultural and communicative features. On the other hand, participants highlighted that grammar teaching and the presence of a teacher are absent in informal learning, which makes it insufficient to learn English. For that reason, both informal and formal English learning should be considered.